Bridging biology and technology: the rise of 3D bioprinting advancements in infection research - Mohammadi, Sajad; Unger, Wendy W. J.; Ferrari, Aldo; Sanchini, Caterina; Ruocco, Giancarlo; D’Alessandro, Salvatore (Frontiers in Bioengineering and Biotechnology, 2026)
The outbreak of infectious diseases and rapid pathogens’ evolution have highlighted the urgency for developing new therapeutics to protect public health and the economy from massive loss. Drug discovery for infectious diseases involves a multi-stage and multi-disciplinary pipeline, often leading to increased risk and mortality due to the prolonged course. However, advancements in technology have been reshaping the field by offering alternative in vitro models—facilitating drug discovery, studying the mechanism of infectious diseases, and developing patient-specific solutions. Recently, 3D bioprinting has been emerging as a revolutionary technology that enables researchers to precisely create custom 3D constructs that mimic human physiology and can be used as either platforms for delivering therapeutics and/or cells locally or in vitro tissue models for drug screening. Herein, we shed light on recent advancements in the use of 3D bioprinting technologies to introduce platforms employed for fabricating 3D structures to control and study infectious diseases.